2009
DOI: 10.26719/2009.15.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Helicobacter pylori in Nahavand: a population-based study

Abstract: In this cross-sectional study, we evaluated H. pylori seroprevalence and the relevant factors in 1518 people aged ≥ 6 years from the general population of Nahavand, western Islamic Republic of Iran. Questionnaires covering sociodemographic variables were completed by interview. Blood samples were taken from each individual. Sera were tested for anti-H. pylori IgG using commercial enzyme immunoassay. Overall, seroprevalence of H. pylori was high, 71.0% (95% CI: 69.0%-73.0%). There was a gradual increase with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
3
19
1
Order By: Relevance
“…Although poor sanitation, such as the lack of sanitary services at home, is believed to be an important risk factor for H. pylori infection (Dube et al, 2009). Anomalies were found by other investigators also, showing that hygienic practice has no significant effect on the seroprevalence of H. pylori (Alizadeh et al, 2009). Poor association between seroprevalenec and socio-economic status in the present study is consistent with many other studies (Dube et al, 2009;Dorji et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although poor sanitation, such as the lack of sanitary services at home, is believed to be an important risk factor for H. pylori infection (Dube et al, 2009). Anomalies were found by other investigators also, showing that hygienic practice has no significant effect on the seroprevalence of H. pylori (Alizadeh et al, 2009). Poor association between seroprevalenec and socio-economic status in the present study is consistent with many other studies (Dube et al, 2009;Dorji et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…This increase in prevalence with age is attributed to annual increase in the rate of infection (Goodman et al, 1996) and birth cohort effect (Banatvala et al,1993 Alvarado-Esquivel, 2013;Dirji et al, 2013). On the other hand, Alizadeh et al (2009) reported that the prevalence of H. pylori was higher in females than males, while Valliani et al (2013) found out that the prevalence was higher in males than females. In this study the prevalence of H. pylori was slightly higher in females than males.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Iran with a high incidence of GC ranks fourth in Asia, after China, Japan and Korea respectively (Fujisawa et al, 1999;Wang and Wang, 2003;Derakhshan et al, 2004;Yim et al, 2007;Alizadeh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, seroepidemiological studies showed that 46-78% of children are infected with H. pylori (1)(2)(3)(4)(5)(6)(7). Therefore, use of non-invasive and invasive diagnostic methods of symptomatic children is important (8,9).…”
Section: Introductionmentioning
confidence: 99%